Retracing the investigation - Snell, Tyler Anne (Snell, Tyler Anne. Saving Kelby Creek series., 2022)
Alabama sheriff and widower Jones Murphy must protect Cassandra West and their unborn child after Cassandra's own investigation unearths a long-buried secret.